Electroconvulsive therapy increases brain volume in major depression: a systematic review and meta‐analysis. (29th April 2018) - Gbyl, K.; Videbech, P.
Abstract : Objective: The main purpose of this review was to synthesise evidence on ECT's effects on brain's structure. Method: A systematic literature review of longitudinal studies of depressed patients treated with ECT using magnetic resonance imaging (MRI) and meta‐analysis of ECT's effect on hippocampal volume. Results: Thirty‐two studies with 467 patients and 285 controls were included. The MRI studies did not find any evidence of ECT‐related brain damage. All but one of the newer MRI volumetric studies found ECT‐induced volume increases in certain brain areas, most consistently in hippocampus. Meta‐analysis of effect of ECT on hippocampal volume yielded pooled effect size: g = 0.39 (95% CI = 0.18–0.61) for the right hippocampus and g = 0.31 (95% CI = 0.09–0.53) for the left. The DTI studies point to an ECT‐induced increase in the integrity of white matter pathways in the frontal and temporal lobes. The results of correlations between volume increases and treatment efficacy were inconsistent. Conclusion: The MRI studies do not support the hypothesis that ECT causes brain damage; on the contrary, the treatment induces volume increases in fronto‐limbic areas. Further studies should explore the relationship between these increases and treatment effect and cognitive side effects.